A cross-sectional study of how environmental and school variables shape schoolchildren's motor competence - Araújo, Giovanna (2025)
Motor competence is an important component of children's physical development, influencing their participation in many physical activities and long-term health outcomes. Environmental affordances also influence motor behavior levels, especially in young children, but limited investigations still explore their specific impact on school-aged children in underrepresented regions. This cross-sectional investigation examined the relationship between motor competence and affordances in home and school environments among 117 children aged 6 to 10 years in North Brazil, with a particular focus on sex differences. The Affordances for Motor Behavior of Schoolchildren (AMBS) questionnaire assessed environmental opportunities, while the Motor Competence Assessment (MCA) evaluated stability, locomotion, and manipulation skills. The Kolmogorov–Smirnov test did not confirm the data normality. Spearman correlations, Mann-Whitney U tests, and multiple linear regressions were applied to determine associations between affordance levels and motor competence scores. Findings revealed weak-to-moderate positive correlations between home and school affordances and motor competence components, particularly in girls. Regression analysis indicated that body mass index negatively impacted motor competence (B = -1.269, p = 0.02), suggesting that higher levels of body mass index may decrease performance levels. Interestingly, while boys typically outperform girls in motor skills, no significant sex differences were found in motor competence levels, possibly due to increased sedentary behavior and screen time post-pandemic. The results underscore the importance of fostering enriching environmental conditions that promote motor skill development, especially for girls. These findings highlight the need for targeted interventions that enhance environmental affordances in both home and school settings to improve children's motor competence.